Development a Recombinant Protein (CrFSH) as a Reproductive Hormone for the Assisted Reproduction of Dairy Cows - Xinxi Qin; Haisen Zhang; Tian Liu; Zhenliang Cui; Kangkang Gao; Pengfei Lin; Yaping Jin (Animals)
Follicle stimulating hormone (FSH) stands as one of the most prevalently used reproductive hormones in the field of animal-assisted reproduction. Conventionally, pituitary FSH is sourced from the heterologous pituitary glands of pigs and sheep procured from slaughterhouses, and it typically exists in the form of crude FSH. The specific challenges inherent in FSH-based assisted reproduction drugs has significantly spurred the interest in exploring novel alternatives, aiming to reduce the reliance on these traditional sources in relevant production processes. In this study, the α- and β-FSH genes were retrieved from pituitary cDNA libraries. These genes were selected to construct a recombinant protein—the novel cow recombinant FSH (CrFSH)—through the application of the homologous recombination method. Notably, the β-subunit was extended by a carboxy-terminal peptide (CTP). After successfully integrating the two genes into Chinese hamster ovary (CHO) cells, the recombinant protein (approximately 33 kDa) in the culture supernatant was detected using Western blotting (WB). The results of the GCs proliferation experiment indicated that both 1.2 µg/mL pFSH and 20–20,000 ng/mL CrFSH could significantly promote the proliferation of GCs in vitro. Remarkably, on the 4th day after treatment, 20 ng/mL of CrFSH had a higher GCs proliferation rate than 1.2 μg/mL of pFSH (p < 0.001). Additionally, cyclic adenosine monophosphate (cAMP) induction assay in GCs unequivocally confirmed that CrFSH possesses superior activity compared to pFSH. These findings underscore that this recombinant protein holds great potential as a promising candidate for FSH production in assisted reproduction approaches for dairy herds.